Selection for resistance to the herbicide imazethapyr in somaclones of soyabean - Taregyan, M.R.; Mortimer, A.M.; Putwain, P.D.; Collin, H.A. (Wiley, 2001)
Cultivars of soyabean [Glycine max (L.) Merr.] resistant to the herbicide imazethapyr were identified by suspending the roots of 5‐day‐old seedlings in nutrient culture containing 2.5 mg a.i. L–1 imazethapyr and then comparing the inhibitory effect on root length and shoot dry weight. The four most resistant cultivars were subsequently screened as regenerating tissue cultures in a medium containing 2.0 mg a.i. L–l imazethapyr to select somaclonal cells with increased resistance. Surviving portions of cultures were regenerated to give shoots, the plants isolated, allowed to flower and seed. These progeny were then used for further seed multiplication and seedlings from this latter generation were exposed to imazethapyr in vivo and callus and cell suspension cultures derived from these seedlings were exposed to imazethapyr in vitro. A reduction in the inhibitory effect of the imazethapyr was noted in the somaclone seedlings and tissue cultures. However, measurement of acetolactate synthase (ALS) activity showed no differences among the parent cultivars and in the selected somaclones in this trait.